Mechanism study of ubiquitination in T cell development and autoimmune disease - Yu, Hui; Yang, Wenyong; Cao, Min; Lei, Qingqiang; Yuan, Renbin; Xu, He; Cui, Yuqian; Chen, Xuerui; Su, Xu; Zhuo, Hui; Lin, Liangbin (Frontiers in Immunology, 2024)
T cells play critical role in multiple immune processes including antigen response, tumor immunity, inflammation, self-tolerance maintenance and autoimmune diseases et. Fetal liver or bone marrow-derived thymus-seeding progenitors (TSPs) settle in thymus and undergo T cell-lineage commitment, proliferation, T cell receptor (TCR) rearrangement, and thymic selections driven by microenvironment composed of thymic epithelial cells (TEC), dendritic cells (DC), macrophage and B cells, thus generating T cells with diverse TCR repertoire immunocompetent but not self-reactive. Additionally, some self-reactive thymocytes give rise to Treg with the help of TEC and DC, serving for immune tolerance. The sequential proliferation, cell fate decision, and selection during T cell development and self-tolerance establishment are tightly regulated to ensure the proper immune response without autoimmune reaction. There are remarkable progresses in understanding of the regulatory mechanisms regarding ubiquitination in T cell development and the establishment of self-tolerance in the past few years, which holds great potential for further therapeutic interventions in immune-related diseases.